O papel do psicólogo escolar frente ao uso de tecnologias da informação e comunicação na educação básica - Carneiro, Pedro Braga (2025)
This is a descriptive and explanatory research, with a qualitative approach, which aims to understand the role of school psychologists in the use of Digital Information and Communication Technologies (ICTs) in Brazilian Basic Education. The initial problem is the growing development and use of these technologies in the school context under an alienating logic of capitalism, as if technological artifacts in themselves represented an ideal of progress and development to be achieved in pedagogical practices, but which end up impacting an encapsulated subjectivity of students and education workers. The hypothesis is that the school psychologist can collaborate significantly with the educational community to overcome the use of ICTs in the market logic, and contribute to thinking of technology as part of the transformative process of a libertarian education. The theoretical framework of the research is structured from the field of Science, Technology and Society (STS), from the perspective of the Critical Theory of Technology, Historical-Cultural Psychology and Historical-Critical Pedagogy. Based on the interfaces between these fields, we sought to verify, through questionnaires, the understandings and practices of school psychologists related to ICTs. The responses were examined through the analysis of meaning, establishing four cores of meaning: relations between technology and social values; technology and work processes; technology and human development; and the role of psychology. As a result, we note the concern of school psychologists regarding the use of ICTs in Basic Education, realizing the importance of contributing to the reflection on the subject with the educational community, even if such debates are not yet being carried out routinely in the daily routine of schools. Finally, we conclude that psychologists, supported by the Historical-Cultural Theory, can contribute quite fruitfully to the reflection on the technologies used in schools in light of the objectives of student development – although schools have not been taking advantage of this potential in their daily routine. However, to this end, it is necessary to qualify psychology professionals in the critical perspective of technology to overcome deterministic and instrumentalist perspectives.